POECILOSTOMATOIDA COPEPODS OF THE FAMILY CORYCAEIDAE DANA, 1852 IN INDONESIAN WATERS - Mulyadi mul (BRIN Publishing (Penerbit BRIN), 2003)
Taxonomic studsy was made on the species of the family Corycaeidae recently collected from 8 sites in lndonesian waters. Twelve species, including 2 subgenus Corycaeus (C. speciosus Dana, 1849, C. crassiusculus Dana, 1849), 4 sllbgenlls Ditrichocorycaeus (c. andrewsi Farran, 1911, C. asiaticusDaM, 1894, C. erythraeus Cleue, 1901, C. lubbocki Giesbreclrt, 1892), 1 subgenus Monocorycaeus (C. robustus Giesbrecht, 1891), 2 subgenus Onychocorycaeus (C. catus Duhl, 1894, C. pacificus Dana, 1894), 1 subgenus Urocorycaeus (C. longistylis Dana, 1849), and 2 species of genus Farranula (F.concinna Dana, 1849, F. gibbula Giesbrect, 1892) were recorded.Descriptions, measurements, and figures are given for all species, along with a review of their distribution over tire world's oceans, witlr taxonotnical remarks, and restricted synonymies.